Study of academic services using the CoBIT framework and IT-infrastructure library - ., Riki; Pataropura, Amesanggeng (International Journal of Engineering and Technology, 2019)
A college that was developed with form and structure of the new, requires a lot of support, including information technology support in achieving new goals. Academic Services as an essential service at a community college should also play a role in achieving these goals. Good management of IT can further accelerate the achievement of organizational goals, for that IT should be on notice and well managed. In connection with IT governance, need to use a good standard to look at existing IT management. as one tool in the measurement of IT governance can be used to view IT governance there. Domain Delivery and Support (DS) and Monitor and Evaluate (ME) is just done at the moment, because the organization was forming a new structure and form. Data collection begins with knowing the vision, mission and goals of the new organization, then proceed to analyze the processes that have the domain DS and ME to determine the level of maturity of these processes. In addition to the process of data analysis was also performed using the data collection questionnaire to determine the current level of maturity (current maturity) and the expected level of maturity (expected maturity).Â